Design of Financial Incentive Programs for Smoking Cessation: A Discrete Choice Experiment. Issue 10 (15th February 2022) - Breen, Rachel J; Palmer, Matthew A; Frandsen, Mai; Ferguson, Stuart G
Abstract: Introduction: Financial incentive programs promote smoking cessation. However, the incentive amount which should be provided—and how this may interact with other program characteristics—is unknown. The objective of this study was to evaluate the influence of the design of incentive programs for smoking cessation on current smokers' perceptions of programs and willingness to enroll. Method: An online discrete choice experiment was conducted amongst adult current smokers residing in the United Kingdom ( N = 430). Hypothetical incentive programs were described using five attributes (incentive amount, incentive type, frequency of sessions, reward schedules, program location). Participants responded to a series of choice sets comprised of two hypothetical programs. For each set, participants selected their preferred program. They then specified whether they would enroll in their preferred program if it were available. Analyses also considered the effect of participant income on preferences. Results: Overall, participants preferred higher amounts over lower amounts, cash over vouchers, healthcare settings over workplaces, and consistent amounts over an escalating schedule. One session per week was the most preferred session frequency. Willingness to enroll increased quadratically with the incentive amount, although this increase slowed for higher amounts. Although middle- and high-income smokers preferred slightly higher amounts (cf. low-income participants), enrollment choices did not differ by income. Conclusion: The characteristics of incentive programs influence smokers' perceptions of programs and willingness to enroll. Higher amounts may encourage greater enrollment rates, but there will likely be a ceiling point beyond which increasing the incentive amount does not meaningfully increase enrollments. Implications: There is increasing evidence incentive programs aid smoking cessation. Yet, the variety in previous program designs means how to best structure programs, including optimal incentive amount and the impact of the design on potential enrollment rates, remains unclear. This study suggests enrollments may be highest when incentive amounts are higher, rewards of a consistent amount in cash are provided, and sessions occur once per week in a healthcare setting. Although higher-income participants may desire higher incentive amounts compared to lower-income participants, this may not translate into differences in willingness to enroll.